Adipokine concentrations in lipoaspirates may have a role in wound healing - Christian Herold; Stefan Engeli; Bibiana Beckmann; Peter M. Vogt; Hans-Oliver Rennekampff (Indian Journal of Plastic Surgery)
Objectives: In addition to its use as a volume filler, fat grafting may have a potential role in wound healing based on the concentration of growth factors in the lipoaspirate. In this study, we compare the quantitative and qualitative concentration of the various growth factors and adipokines using the Shippert or the Coleman techniques to prepare the lipoaspirate. Methods: We measured leptin, adiponectin and the growth factors, i.e., acidic fibroblast growth factor (aFGF), basic FGF (bFGF), keratinocyte growth factor (KGF), bone morphogenetic protein-2 (BMP-2) and vascular endothelial growth factor (VEGF) by ELISA in solid and liquid fractions obtained with both techniques in human fat obtained with Coleman technique and Shippert technique. Results: All of these peptides, except BMP-2, were detected in relevant quantities in the solid fraction. The Coleman but not the Shippert technique resulted in statistically higher adiponectin concentrations in the solid tissue fraction. The other four growth factors occurred in significantly higher concentrations in the solid fractions compared to the liquid fractions, independent of the processing technique. Conclusion: In summary, we demonstrated that KGF, aFGF, bFGF and VEGF, as well as leptin and adiponectin, are contained in fat suspensions obtained by liposuction and in the supernatant. Only the concentration of adiponectin was in the range reported to contribute to wound healing.